Exploring the association between social and emotional skills and online social experiences: a network analysis and latent profile analysis - Yang, Xiaoli; Yan, Junyu; Cui, Ziqian (Frontiers in Psychiatry, 2025)
With the widespread use of social media, online social experiences have become increasingly influential on the mental health of young people. However, how individuals’ socio-emotional skills modify these experiences remains unclear. This study conducted a survey of 1,422 Chinese university students and applied network analysis and latent profile analysis to explore the relationship between socio-emotional skills and online social experiences. The results showed that socio-emotional skills had a significant positive correlation with positive online social experiences and a significant negative correlation with negative online social experiences. Among these skills, stress resilience may serve as a key dimension for enhancing overall socio-emotional competence. Therefore, interventions targeting stress resilience could be particularly effective in helping individuals strengthen their broader socio-emotional skills, thereby improving their online social experiences. Additionally, the study found that positive and negative online social experiences are two distinct constructs, suggesting that intervention strategies should address them separately. These findings provide a theoretical foundation for developing targeted interventions to improve young people’s online social experiences and promote their mental well-being.